Razia Khan Amin: A Bangladeshi writer in English - Hasan, Md. Mahmudul (2022)
Razia Khan Madam is part of a literary heritage that is rich and varied. We need committed, competent and confident researchers, especially from within Bangladesh, to analyse, evaluate and explore the full extent of its breadth and depth. It is my hope that we–current and future researchers–will be able to do justice to the legacies of Razia Khan Madam and her likes who are still largely understudied and under-represented in literary scholarship.